2009
DOI: 10.1109/tgrs.2008.2010252
|View full text |Cite
|
Sign up to set email alerts
|

Observations and Modeling of a Pine Forest Floor at L-Band

Abstract: Abstract-Recent studies of passive L-band observations over forests have shown that the average canopy transmissivity in temperate coniferous and deciduous forests is on the order of 0.4-0.5. Although the canopy would therefore be expected to transmit a reasonable amount of ground emission, the total emission observed above the canopy shows very little variation with varying soil moisture content. Moist litter present on the forest floor is known to obscure the soil emission. Therefore, more knowledge on the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Over the past few years, some attention has been placed on understanding the microwave signatures of deciduous and coniferous forest floors [8]- [10], [16], [17]. Several field experiments have demonstrated the significance of a forest litter layer in SM retrieval from L-band brightness data [5], [8], [20].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past few years, some attention has been placed on understanding the microwave signatures of deciduous and coniferous forest floors [8]- [10], [16], [17]. Several field experiments have demonstrated the significance of a forest litter layer in SM retrieval from L-band brightness data [5], [8], [20].…”
mentioning
confidence: 99%
“…Laboratory observations of the dielectric properties of litter were made by Kleshchenko et al [21] and Demontoux et al [22]. Grant et al [10] made in situ field observations of forest floor layers in their undisturbed state by sequentially stripping each layer. This was the first investigation to use in situ experimental data in this context.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The gradual dielectric transition from air to soil is represented using a semiempirical effective medium approach. As demonstrated in [24]- [26], a similar approach can also be used for modeling the reflectivity of soils covered with sparse vegetation or litter, provided that scattering is not dominant.…”
mentioning
confidence: 99%
“…Second, a depth of approximately 3 cm litter is presented in this study area. As previous experimental studies [41,42] found, the sensitivity of the above-canopy TB to soil moisture may be substantially attenuated by the presence of litter when the soil is wet. Models for correcting the effects of that layer overlaying the soil have been developed, such as by Della Vecchia et al for needle litter [13], by Schwank et al for deciduous leaf litter [11], and lately by Bircher et al for boreal forest organic layer [26].…”
Section: Discussionmentioning
confidence: 55%